Peran Partisipasi Siswa Dalam Menjaga Kebersihan Kelas Dan Diri Sendiri - TAUFIQ, TAUFIQ (Universitas Sebelas Maret, 2022)
Cleanliness is an important factor in creating a healthy and comfortable learning environment. This article discusses the important role of student participation in keeping the classroom and themselves clean. Through this research, we explored the positive impact of students' active participation on classroom hygiene conditions and the level of awareness of personal hygiene. The research method used involved observation, interviews and questionnaires to gain comprehensive insight into the role of students in maintaining cleanliness.